Birth, attitudes and placentophagy: a thematic discourse analysis of discussions on UK parenting forums - Riley Botelle; Chris Willott (BMC, 2020)
Abstract Background The post-partum consumption of the placenta by the mother (placentophagy) has been practiced since the 1970s in the global North and is seemingly increasing in popularity. Maternal placentophagy is not known to have been practiced in any other time period or culture, despite being near-ubiquitous in other placental mammals. An in-depth qualitative exploration as to the reasons for the practice, its increasing popularity and how it is narratively incorporated into discourses surrounding "ideal" natural and medical births are given in this paper. Methods 1752 posts from 956 users across 85 threads from the parenting forums Mumsnet and Netmums were identified for inclusion. A thematic discourse analysis was performed using NVivo. Results Three main themes were identified: women recounted predominantly positive attitudes towards their own experiences of placentophagy, and they were respectful of others' views and experiences; some had negative views, particularly around the concept of disgust, but again, they were respectful of others' experiences. By far the most common method of consumption of the placenta was encapsulation. Conclusions This paper identifies the motivation for placentophagy to almost universally be for medical benefits, most commonly the prevention or treatment of post-natal depression (PND). Whilst disgust is a common reaction, discussion of risks is rare, and positive experiences outweigh negative ones. The increasing popularity of the practice is ascribed in part to the comparative palatability of encapsulation and the use of the internet to share resources and remove barriers. Parenting forums are important spaces to negotiate normative birth practices, including placentophagy, and act to build communities of women who value personal experience over medical evidence and highly value personal choice and bodily autonomy. Placentophagy is discussed in terms of its relation to natural and medical births with arguments being made using both discourses for and against the practice. This paper argues that placentophagy is practiced as a resistance to medicalisation as an assertion of control by the mother, whilst simultaneously being a medicalised phenomenon itself.